2021
DOI: 10.1007/s13201-020-01348-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of rainfall–runoff parameters models to estimate flows

Abstract: Determinate the runoff of a watershed is a challenge due to the complexity of representing all “inlets” and “outlets” involved in a rainfall–runoff model. Therefore, methodologies applied for this purpose should have a good representation of the variables that most influence in this process. One of the models used to calculate the design flow is the (USDA in Urban Hydrology for Small. Technical release, no 55 (TR-55). Soil Conservation Service. Washigton, DC, http://scholar.google.com/scholar?hl=en&btnG=Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(33 reference statements)
0
1
0
1
Order By: Relevance
“…Sharifi and Hosseini [1] also showed variability in their results obtained using empirical and semiempirical methods. Yogi et al [92] indicated that the models can provide a process that allows for more accurate analyses of drainage in forested mountain catchments, attributing the advantages to a more accurate choice of hydrological parameters.…”
Section: Identification Of Practical Approaches For Estimating the Ti...mentioning
confidence: 99%
“…Sharifi and Hosseini [1] also showed variability in their results obtained using empirical and semiempirical methods. Yogi et al [92] indicated that the models can provide a process that allows for more accurate analyses of drainage in forested mountain catchments, attributing the advantages to a more accurate choice of hydrological parameters.…”
Section: Identification Of Practical Approaches For Estimating the Ti...mentioning
confidence: 99%
“…El número de curva varía de acuerdo con el tipo de suelo y su uso por tanto en caso de cuencas urbanas se debe establecer las áreas residenciales, comerciales, industriales en cada cuenca o área hidrológica urbana (Yogi et al, 2021), incluso es un parámetro que puede variar regionalmente como lo demuestra (Lian et al, 2020) en un estudio con más de 600 eventos de lluvia escorrentía en China. La tabla 2 muestra la clasificación de los usos del suelo usadas en esta contribución.…”
Section: Materiales Y Métodosunclassified